Research helps a tree of gold - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Prunus africana (or Pygeum africanum) grows in a wild state in the mountains of Kenya, Cameroon and Madagascar. Its bark provides a powder, which has been used over the centuries in traditional medicine for treating male prostate problems. The...